NTD-related disease management, disability and Inclusion (DMDI) - Brakel, Wim H van (Henry Stewart Talks, 2019)
Problems for NTD management, Disease management, disability and inclusion (DMDI), DMDI and the WHO International Classification of Functioning, Disability & Health (ICF), The Journey Through Care, DMDI and Universal Health Coverage, Integrating DMDI in NTD programmes, Priorities for DMDI in endemic areas